1998
DOI: 10.1021/ja981201u
|View full text |Cite
|
Sign up to set email alerts
|

Pentacoordinate Siliconate Tetraanionic Molecular Squares. Synthesis, Structure, and Solution Conformation of a Novel Tetraanion−Tetracation Ion Pair

Abstract: A tetraanionic molecular square containing four pentacovalent siliconates is produced in high yield by the condensation of phenyltriethoxysilane and spirocatechol 1. A single isomer, meso 2, is produced from this diastereoselective condensation reaction. The steps leading up to the formation of meso-2 are not known, but the reaction appears to be driven by the insolubility of the tetrakistriethylammonium salt 2a. The tetraanionic macrocycle is a stable salt that undergoes ion-exchange reactions. An ion pair co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…Porosity originates solely from the molecular structure,w hich is independent of processing history. Racemic 1 has also been used as abuilding block for siliconate tetraanionic molecular squares [21][22][23][24] and tetraanionic organoborate squares,aswell as for the synthesis of racemic PIMs. [18][19][20] All PIMs reported to date have been achiral, and all reported studies of materials incorporating 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane (TTSBI(1)) have utilized the racemic form.…”
mentioning
confidence: 99%
“…Porosity originates solely from the molecular structure,w hich is independent of processing history. Racemic 1 has also been used as abuilding block for siliconate tetraanionic molecular squares [21][22][23][24] and tetraanionic organoborate squares,aswell as for the synthesis of racemic PIMs. [18][19][20] All PIMs reported to date have been achiral, and all reported studies of materials incorporating 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane (TTSBI(1)) have utilized the racemic form.…”
mentioning
confidence: 99%
“…
5',6, hereafter LH 4 )

, which is easily obtained in racemic form, is an attractive building block for the construction of functional solids, because of its ready availability, its rigid angularity, and its chirality. [1] Although no X-ray crystallographic data are available, NMR spectroscopy indicates that a single diastereoisomer with C 2h symmetry containing the two L 4À enantiomers in equal numbers is selectively formed. [1] Although no X-ray crystallographic data are available, NMR spectroscopy indicates that a single diastereoisomer with C 2h symmetry containing the two L 4À enantiomers in equal numbers is selectively formed.

…”
mentioning
confidence: 99%
“…[1] Although no X-ray crystallographic data are available, NMR spectroscopy indicates that a single diastereoisomer with C 2h symmetry containing the two L 4À enantiomers in equal numbers is selectively formed. Shea and co-workers have reported that reaction of LH 4 with phenyltriethoxysilane under basic conditions generates tetraanionic molecular squares of composition [(C 6 H 5 Si) 4 L 4 ] 4À , in which the silicon centers have five-coordinate environments that are probably close to square pyramidal with a square O 4 base defined by two L 4À units.…”
mentioning
confidence: 99%
See 2 more Smart Citations